Математическая модель управления информационными потоками в распределенных системах контроля за ядерно-радиационными материалами - Забулонов, Ю.Л.; Буртняк, В.М. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
In the article a mathematical case informative streams frame is resulted in the distributed systems of control after radiation materials. A model is simplified by the process of realization of the tasks decided in the system